1992
DOI: 10.1177/009164719202000208
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Rech Conference Survey on Religious Faith and Professional Psychology

Abstract: The results of an extensive survey of the alumni of three doctoral- and four master's-level Christian graduate training programs in professional psychology are reported. The purpose of the survey was to assess how programs have done in training students in the integration of psychology and Christian faith. A total of 1,548 surveys were mailed out; a return rate of 41.3% limited the conclusiveness of the findings. The sample was found to be morally and religiously conservative; master's alumni were typically mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 6 publications
4
40
0
Order By: Relevance
“…For example, Shafranske and Malony (1990b) surveyed 409 clinical psychologists and found that greater involvement in organized religion correlated .27 with the use of religious and spiritual interventions. Jones et al (1992) conducted a survey of 640 doctoral-and master'slevel clinical psychologists (i.e., those who had master's degrees and those who had doctorates) who identified themselves as explicitly Christian in practice. These authors found that a composite of four religious behaviors (i.e., personal prayer and Bible study, church attendance, participation in church activities, and financial contributions to church) correlated .41 with the use of religious and spiritual interventions in counseling.…”
Section: Therapists' Personal Religiousnessmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Shafranske and Malony (1990b) surveyed 409 clinical psychologists and found that greater involvement in organized religion correlated .27 with the use of religious and spiritual interventions. Jones et al (1992) conducted a survey of 640 doctoral-and master'slevel clinical psychologists (i.e., those who had master's degrees and those who had doctorates) who identified themselves as explicitly Christian in practice. These authors found that a composite of four religious behaviors (i.e., personal prayer and Bible study, church attendance, participation in church activities, and financial contributions to church) correlated .41 with the use of religious and spiritual interventions in counseling.…”
Section: Therapists' Personal Religiousnessmentioning
confidence: 99%
“…More recently, Prest et al (1999), in their survey of 52 student marriage and family therapists, found that 86.3% of the sample believed it was necessary to work with a client's spirituality if a therapist really expected to help the client. Although several studies have found that personal religiousness on the part of the therapist is associated with his or her beliefs regarding the use of religious and spiritual interventions in counseling (DiBlasio & Benda, 1991;Jones et al, 1992;Shafranske & Malony, 1990a), no study to date has examined therapists' professional beliefs, attitudes, and values regarding the use of religious and spiritual interventions in counseling with their actual use of those interventions.…”
Section: Professional Beliefs Attitudes and Values Regarding Religimentioning
confidence: 99%
See 2 more Smart Citations
“…A few research studies have investigated the reported use of religious interventions by psychotherapists (Ball & Goodyear, 1991;Jones, Watson, & Wolfram, 1992;Moon, Willis, Bailey, & Kwasny, 1993;Richards & Potts, 1995;Worthington et al, 1988). However, most of the available research evaluates the use of religious interventions from the perspective of clinicians.…”
mentioning
confidence: 99%